2009
DOI: 10.1164/rccm.200712-1787oc
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transcriptional Regulation of Urokinase-type Plasminogen Activator Receptor Expression in Lipopolysaccharide-induced Acute Lung Injury

Abstract: Rationale: Urokinase-type plasminogen activator (uPA) receptor (uPAR) is required for the recruitment of neutrophils in response to infection. uPA induces its own expression in lung epithelial cells, which involves its interaction with cell surface uPAR. Regulation of uPAR expression is therefore crucial for uPA-mediated signaling in infectious acute lung injury (ALI). Objectives: To determine the role of uPA in uPAR expression during ALI caused by sepsis. Methods: We used Western blot, Northern blot, Northwes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…It binds the uPAR 3′UTR and increases uPAR expression by enhancing uPAR mRNA stability (Bhandary et al, 2009;Shetty, 2005). By comparing the expression of metastasisassociated genes, we found that Akt activation is markedly different between MDA-MB-435 and LvBr2 cells.…”
Section: Discussionmentioning
confidence: 83%
“…It binds the uPAR 3′UTR and increases uPAR expression by enhancing uPAR mRNA stability (Bhandary et al, 2009;Shetty, 2005). By comparing the expression of metastasisassociated genes, we found that Akt activation is markedly different between MDA-MB-435 and LvBr2 cells.…”
Section: Discussionmentioning
confidence: 83%
“…Transgenic mice with a deletion in the uPA gene (uPA 2/2 ) and control mice on the same genetic background (C57B6/129) were described earlier (15). The mice were kept on a 12:12 hour light-dark cycle with free access to food and water.…”
Section: Micementioning
confidence: 99%
“…Extracts from mouse lungs were prepared as described (15,18). Briefly, mouse lungs were separated into small pieces with fine scissors and rinsed three times with PBS.…”
Section: Preparation Of Crude Extract From Mouse Lung and Western Blomentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, investigators studied uPAR expression because of its central role in neutrophil recruitment. This group determined that endotoxin-mediated uPAR expression is mediated through tyrosine phosphorylation of phosphoglycerate kinase and heterogeneous nuclear ribonucleoprotein (29).…”
Section: Pathogenesis Of Ali In Animal Studiesmentioning
confidence: 99%